Implementasi Nilai-nilai Kearifan Lokal Desa Penglipuran dalam Meningkatkan Solidaritas Sosial - Saefullah Aji; Diyah Nur Septiyaningsih; Lilis Nurhalimah; Sindi Pusparani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Indonesia, as a multicultural country, has more than 1,300 ethnic groups with local wisdom that plays a role in maintaining social solidarity. This study examines the implementation of local wisdom in strengthening social solidarity in Penglipuran Village, Bali, using a qualitative approach with case studies. Data were collected through interviews, participant observation, and documentation studies. The results of the study indicate that mutual cooperation, the social sanction system, and the role of women in traditional activities contribute to social cohesion. The principle of Tri Hita Karana is the main foundation in maintaining the balance of social relations. This finding emphasizes the importance of local wisdom in facing the challenges of globalization, so that its preservation needs to be continuously pursued.